A cross-sectional study to assess the pattern of work-related musculoskeletal disorder among class-IV workers of tertiary care centres in central India - Soni, Anamika; Trivedi, Anshuli; Verma, Gyan Prakash (International Journal Of Community Medicine And Public Health, 2024)
Background: Musculoskeletal disorders (MSDs) are typically characterized by persistent pain and limitations in mobility and dexterity. They are highly prevalent and are the leading cause of severe long-term pain and physical disability. Providing stress-management training, encouraging regular breaks, and offering physical therapy and other treatments can alleviate the physical symptoms of work-related MSDs (WMSDs). Objectives were to assess the prevalence and patterns of WMSDs among class-IV workers and to identify the key factors contributing to WMSDs. Methods: The study was conducted at the Hamidia Hospital and Gandhi Medical College Bhopal. 350 class IV workers were selected using random sampling, and data were collected by direct interview. Results: Among all housekeeping staff, 82% showed symptoms of MSDs. Pain was predominantly reported in the lower back (49.3%), followed by the lower leg (32.9%). Among the 350 participants, 72 experienced mental stress manifested as difficulty falling asleep, restlessness, and anxiety. Gutkha, followed by smoking, was the most common substance abused by Class IV workers, which correlated with musculoskeletal pain. Participants with a BMI<18.5 and 25-29.99 reported more MSD pain compared to those with a normal BMI (18.5-24.99). Additionally, workers who did not exercise or exercised only 1-2 times a month experienced higher levels of pain. Conclusions: Class IV workers face physically demanding tasks, so regular breaks should be advised. Promoting literacy can aid in the prevention and early detection of MSDs. Basic interventions and counselling are essential to prevent chronic pain, mental stress, and the development of MSDs.